2005
DOI: 10.1037/h0088897
|View full text |Cite
|
Sign up to set email alerts
|

Child-Centered Group Play Therapy with Children with Speech Difficulties.

Abstract: efficacy of child-centered group play therapy with pre-kindergarten and kindergarten children with speech difficulties as an intervention strategy for improving specific speech problems in the areas of articulation, receptive language, and expressive language. A second purpose was that of determining the efficacy of child-centered group play therapy in improving self-esteem, positive social interaction, and in decreasing anxiety and withdrawal behaviors among pre-kindergarten and kindergarten children with spe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
37
0
2

Year Published

2010
2010
2018
2018

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 63 publications
(41 citation statements)
references
References 47 publications
(63 reference statements)
2
37
0
2
Order By: Relevance
“…Through this approach, they can develop their social interest and socialize with their peers. In line with this statement, Danger (2003) points out that the group play therapy has been related to the improvement of social acceptance. A child, who is assumed to have a good social acceptance, possesses proximity and familiarity with his/her surrounding that affects on the interpersonal attractiveness (Berscheid & Walster, 1978).…”
Section: Introductionmentioning
confidence: 52%
See 1 more Smart Citation
“…Through this approach, they can develop their social interest and socialize with their peers. In line with this statement, Danger (2003) points out that the group play therapy has been related to the improvement of social acceptance. A child, who is assumed to have a good social acceptance, possesses proximity and familiarity with his/her surrounding that affects on the interpersonal attractiveness (Berscheid & Walster, 1978).…”
Section: Introductionmentioning
confidence: 52%
“…According to Bevins (in Danger, 2003), the game process demands the children learn to accept and to be accepted by other people. Accordingly, the popular and the controversial children will understand more about the isolated children, and vice versa.…”
Section: Table 1 Descriptive Statistics Of Interpersonal Attractivenessmentioning
confidence: 99%
“…The current study sought to investigate whether similar benefits to that of play therapy interventions were found for children who engage in non-directive play with trained and supervised school staff. Research indicates positive effects of play therapy interventions on children's behaviour with reference to a range of problem areas such as anxiety and behavioural problems (Fall, Navelski, & Welch, 2002;Draper, White, O'Shaughnessy, Flynt, & Jones, 2001;Danger & Landreth, 2005;Packman & Bratton, 2003). For example, play therapy has been successful in reducing anxiety symptoms in children with special educational needs (Fall et al, 2002) and in reducing both anxiety and depression in discouraged or struggling children (Draper et al, 2001) and pre-adolescent children (Packman & Bratton, 2003).…”
Section: Introductionmentioning
confidence: 94%
“…Another recent treatment study, conducted by some of the same authors and using almost identical study design as Bratton et al (2013), provided evidence for Adlerian play therapy as another level 2 treatment for disruptive behavior (Meany-Walen, Bratton, & Kottman, 2014). While the remainder of play therapy interventions published since the year 2000 remain at level 4, there has been a growing number of 21st-century experimental and quasi-experimental research studies indicating positive treatment effects for several presenting problems, including internalizing problems (Packman & Bratton, 2003), ADHD (Ray, Schottelkorb, & Tsai, 2007), trauma (Schottelkorb, Doumas, & Garcia, 2012;Tyndall-Lind, Landreth, & Giordano, 2001;Shen, 2002), academic problems (Blanco & Ray, 2011), delayed language skills (Danger & Landreth, 2005), teacher-child relationship problems (Ray, 2007;Ray, Henson, Schottelkorb, Brown, & Muro, 2008), and adaptation to medical problems (Bloch & Toker, 2008;Jones & Landreth, 2002;Li & Lopez, 2007;Tsai et al, 2013). The empirical evidence for medical play therapy is particularly notable for its methodological strengths and promising results.…”
Section: Play Therapy Research In the 21st Century And Individual Stumentioning
confidence: 99%
“…This review of 21st century peer-reviewed and published nonfilial play therapy studies identified 18 experimental studies (Blanco & Ray, 2011;Bratton et al, 2013;Carpentier, Silovsky, & Chaffin, 2006;Danger & Landreth, 2005;Fall et al, 2002;Garza & Bratton, 2005;Jones & Landreth, 2002;Li et al, 2008;Meany-Walen et al, 2014;Packman & Bratton, 2003;Paone, Packman, Maddux, & Rothman, 2008;Ray, 2007;Ray et al, 2007Ray et al, , 2008Schottelkorb et al, 2012;Shen, 2002;Tsai et al, 2013;Wang Flahive, & Ray, 2007). While randomization is often difficult when designing an intervention-based research design, play therapy researchers have clearly responded to the need for RCTs.…”
Section: Group Designmentioning
confidence: 99%